Draft Genome Sequence of Ligilactobacillus salivarius TUCO-L2, Isolated from Lama glama Milk - Albarracín, Leonardo Miguel (2020)
Ligilactobacillus salivarius TUCO-L2 was isolated from llama milk in Bio-Bio, Chile, and sequenced with the Illumina MiSeq platform. TUCO-L2 genome sequencing revealed a genome size of 1,600,747 bp with 1,691 protein-coding genes and a GC content of 33%. This draft genome sequence will contribute to a better understanding of the microbiome of llama milk.